Voting by monetary policy committees: Evidence from the CEE inflation-targeting countries - Alexander Jung; Gergely Kiss (Magyar Nemzeti Bank, 2012)
The aim of this paper is to study preference heterogeneity in monetary policy committees of inflation-targeting (IT) countries in Central and Eastern Europe (CEE) during the period 2005-2010. It employs (individual) voting records of the Monetary Council of the Magyar Nemzeti Bank (the central bank of Hungary) and of the Monetary Policy Council of the National Bank of Poland. Preference heterogeneity in committees is not directly observable. Therefore, we pursue an indirect measurement and conduct an econometric analysis based on (pooled) Taylor-type reaction functions estimated using real-time information on economic and financial indicators and voting records. Recent evidence for the monetary policy committees (MPCs) of advanced economies (see Besley et al., 2008; and Jung, 2011) suggests that preference heterogeneity among its members is systematic. Unlike for monetary policy committees of advanced countries, the present paper finds preference heterogeneity to be random for both the members of the Monetary Policy Council of the National Bank of Poland (NBP), and the members of the Monetary Council of the Magyar Nemzeti Bank (MNB). But, similar to the committees of advanced economies, the diversity of views on the inflation forecast is measurable in both committees. A separate cluster analysis shows that different preferences of MPC members may be attributable to their status (chairman, internal member, external member) and that members may also differ in their desired response to changes in the economic outlook.
Keywords: C23; D72; D83; E58; 330; central banking; monetary policy committee; inflation targeting; collective decision-making; voting; preferences; pooled regressions